An application of the health action process approach to physiotherapy rehabilitation adherence. (November 2014) - Clark, Heather; Bassett, Sandra
Abstract This study tested the utility of an extended version of the health action process approach (HAPA) to explain the attitudinal and behavioural processes contributing to rehabilitation adherence and ultimately rehabilitation outcomes in physiotherapy patients. The HAPA focuses on self-efficacy, action and coping planning and their relationships to behavioural intentions and actual behaviour. A one group prospective design was employed in which 20 participants with soft tissue injuries of the shoulder were followed for the first four weeks of their clinic- and home-based physiotherapy. Participants enrolled in the study after their first physiotherapy clinic appointment, at which time they completed questionnaires measuring the motivational HAPA constructs and shoulder function. Action and coping plans were then made with assistance of the researcher. Adherence behaviours were measured throughout the study, and at the end the volitional stage HAPA constructs, action self-efficacy and shoulder function were assessed. Moderate to strong correlations occurred between the self-efficacies and behavioural intentions, behavioural intentions and adherence behaviours, and adherence behaviours and post-study shoulder function. These findings support the extension of the HAPA model to include the functional outcomes for soft tissue injuries of the shoulder. Its true value will nevertheless only be realized in a longer duration study with a larger sample size.